Od człowieka racjonalnego do emocjonalnego. Zmiana paradygmatu nauk ekonomicznych - Krzysztof Wach (Jesuit University Ignatianum in Krakow, 2010)
The paper discusses the concept of an economic man in economics and management. The concept of "homo oeconomicus" assumes the full rational behaviour of a deciding man and was applied in classical and  neoclassical theories. Based on resent findings of the neuronal, cognitive and behavioural sciences, a the concept of an emotional man seems to be better. Thus some scholars believe that "homo sapiens oeconomicus" emerges as an alternative to "homo oeconomicus".  The paper present the chronological survey of the evolution of the above mentioned concepts resulting in the change of the paradigm.